Leprosy Mimicking Common Rheumatologic Entities: A Trial for the Clinician in the Era of Biologics - Deepak Rath; Shrinath Bhargava; Bijit Kumar Kundu (Case Reports in Rheumatology)
Rheumatoid arthritis and seronegative spondyloarthritis, which make up the lion’s share of cases attending a rheumatology clinic, are relatively easy to diagnose. However, when an entity of infective aetiology like leprosy known to be a great mimic of different autoimmune conditions presents with features similar to these, the possibility of it being diagnosed at the outset is very slim indeed. The ease with which the diagnosis of leprosy can be missed assumes sinister proportions as the use of disease modifying agents can have deleterious effects in these patients. In the era of increasing availability and use of biologic disease modifying agents, it is imperative not only to actively rule out the presence of leprosy but also to make it a part of the prebiologic screening of patients in whom biologics are being planned to be administered, especially in leprosy endemic areas.